Thru the years to '76 - Bicentennial West Fargo-Riverside History Book Committee; J&M Printing (North Dakota State Library, 1977)
A history of West Fargo, North Dakota including family biographies. 252 pages : illustrations, photographs 26 cm. Their son, Richard, was married Sept. 5, 1975 to Amy Beveridge of Apple Valley, Minn. Many Armour people were transferred from here when the plant closed. Emmett was kept here as cashier for Armours with office at the Union Stockyards. We then moved from the Village and bought a home in Southwest Fargo. Emmett was one of ten men who organized the Fireside Investment Corporation. These men instigated the building of the Sheyenne Plaza and the First National Bank. When Armours transferred all of their book work to St. Paul, Emmett was retired after 37 years with the company. He then went to work for Blakeley Cattle Co. and worked there until his death in 1967. JOHN WILLIAMS FAMILY John "Busty" Williams came to West Fargo from Lidgerwood, N. Dak. in 1957. John and Ardis Trehbeath were married in 1963 and they have one son, Danny, who was born in 1967. Danny is a third grader at the South Elementary School. Busty is employed as a cattle salesman for Farmers Union Marketing. Busty and Ardis are members of the West Fargo Presbyterian Church and reside at 843 Oak St., West Fargo. Busty is a member of the Lions Club and at the present time is serving his second term as a West Fargo City Commissioner. EDWARD R. PETERSON FAMILY Edward and I moved to West Fargo in June, 1968. We had farmed in Ransom County south of Fort Ransom since we were married in 1946. Edward, the son of Anton and Jennie Peterson, grew up at Englevale, ND and graduated from high school there in 1936. That summer and the next year he spent working with the CCC. He then joined the ND National Guard. He was working in Detroit, Mich, when World War II broke out, and the National Guard was activated. They were organized into the 776th Tank Destroyer Btn. and were sent overseas to Africa in Dec. 1942. Ed returned from Europe after 472 years of overseas duty, and when the war was over. While farming he worked for the ASCS part time, was a member of the Stiklestad Lutheran Church, the VFW of Fort Ransom, the Democratic Party of Ransom County, and the Farmers Union. When he retired from farming he went to work for the Bureau of Reclamation Survey Team at Oakes, ND. He died of a heart attack in December, 1969 at the age of fifty. I grew up at Fort Ransom, the daughter of Hilmar Anderson, who still makes his home there. I graduated from high school at Fort Ransom in 1942, and attended school at the Valley City State College for one year. I then came to Fargo, and worked for Armour .and Company until July, 1946, when Edward and I were married. Edward and I met when I was a Senior in high school, and when he returned from the service in October, 1945 we resumed our acquaintance. The first year we were married I taught school at the Hanson Consolidated School. While my family was growing up I kept active with church and Ladies Aid activities. I also was a Farmers Union Junior Education Leader for 13 years, a 4H Leader, worked with the Democratic Party, and was a clerk on the local election board for a number of years. When we moved to West Fargo, I worked for Crescent Jewelers. In 1970, I changed job in order to be closer to home and I worked for the West Fargo Insurance Agency. In December, 1974, I took a civilian job with the Armed Forces. Our family joined the Faith Lutheran Church in West Fargo, and I also have transferred my membership to the VFW Auxiliary. Gene, the oldest of our six children, joined the Army National Guard shortly after graduating from High School. He lived with us in West Fargo while being employed at the Coop Elevator at Prosper. He left there to be Assistant Manager at Brandon, Minnesota. At present he is Manager of the Hadler Grain Co. and lives at Ada, Minn, with his wife, Jean and his three children, Randy, Sara and Jason. Elaine graduated from high school in Lisbon, ND, then attended Dakota Business College. She worked at the American State Bank in Moorhead and the Armed Forces Examining and Entrance Station. She and James Hanson were married and lived in West Fargo until James was transferred to Ft. Carson. They moved to Colorado Springs in Sept. 1974. Stanford graduated from high school at Lisbon also and attended the State School of Science at Wahpeton for two years, before he enlisted in the Navy. He spent most of his time in Washington, DC with trips to Iceland and Alaska. He is now stationed in Guam. Yolanda was the first one to graduate from high school in West Fargo, in June, 1969. She attended the Dakota Business College, and also took a course at the Atlantic Airline School in Kansas City. At present she is employed at the Fargo Wire Company, and lives at home with her son, Kenneth. 91 Scanned with a Zeutschel Zeta book scanner at 300 dpi. Edited with Multi-Page TIFF Editor.